Ideal culture conditions for Dicyma pulvinata conidia mass production - Melo, Débora Ferreira; Mello, Sueli Corrêa Marques de (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to set up ideal conditions for conidia mass production of Dicyma pulvinata. Four isolates were compared in terms of their growth and conidia production on various substrates (grains of parboiled rice, common rice, maize and wheat, besides chipped maize and rice husk), temperatures (19, 22, 25, 28 and 31oC), growth containers (aluminum trays, polypropylene bags and Erlenmeyers) and light regimes (continuous darkness, 6 and 12 hours of light/darkness, and continuous light). Temperature effects on conidia germination capacity were also evaluated. The experiments were done in randomized complete block designs, in factorial arrangements (isolates x treatments – substrates, containers, temperatures and light regimes), with four replicates. In general, parboiled rice and polypropylene bags provided the best development of the fungus. Complete darkness and 6 hours of light increased mycelial growth, whereas continuous light favored sporulation. All tested temperatures favored the cultures of the fungus, except 31oC. Temperatures between 19 and 25oC ensure spore germination of more than 76%.